ERROR ANALYSIS IN THE NEWS TEXTS MAIN PAGE OF JAMBI EKSPRES DAILY NEWSLETTER - Dimas Anugrah Adiyadmo; Aceng Rahmat; Ratna Dewanti (Program Studi Pendidikan Bahasa Program Pascasarjana Universitas Negeri Jakarta, 2019)
Abstract Mass media is one of the media that greatly influences the understanding of human language and is one of the pathways for developing good and correct guidance and development of Indonesian. Errors are often found in the process of forming words or errors that have the potential to change the meaning and shape of words. This article is based on Mini Research results on the topic; Error Analysis in the News Texts Main Page Newspapers (Descriptive-Analytical Study of Jambi Ekspres Daily News Texts December 26, 2018). This study focuses on the errors of the standard Indonesian language, namely sentences that have ambiguity or mean and ambiguous meaning, words that are influenced by various conversational languages, words that do not have the correct spelling, words that are influenced by foreign languages, and words that do not match the context of the sentence. Data obtained in the form of words, speech or behaviour, are not expressed in the form of numbers or statistical numbers but rather in a qualitative form, by giving an image according to what it is. The aim is to describe the symptoms that exist in the data without giving any form of treatment to the subject to be studied. Keywords: language errors, written language, standard language, spelling, newspapers.